THE EFFICACY OF CHAIN PICTURES IN TRAINING EFL STUDENTS TO WRITE NARRATIVE PARAGRAPHS - WIDYA RIZKY PRATIWI (Jurnal Bahasa Lingua Scientia, 2021)
Writing skill is very crucial in learning the language. However, it is the most challenging skill for learners because of the complexity of various nuances. Learners find it is hard to produce well-written essays, primarily narrative paragraphs. Therefore, this study aimed to discover the efficacy of using chain pictures in writing narrative paragraphs to Indonesian EFL students. This study population was the second year students of Senior High School 4 Bulukumba, South-Sulawesi, Indonesia. Thirty students were selected as the sample. The data were collected through the pre-experimental method by using pre and post-test design. The result showed that the students' writing skills were significantly improved after training them by using chain pictures. The analysis result shows that students' mean score in the pre-test was 56,87, categorized as poor writing skills. In contrast, the students' mean score in the post-test was 74,13, classified as good writing skill of narrative paragraph. The t-test value was also higher than the t-table value, which was 8,25 > 2.045. Thus, it is recommended to use chain pictures in the English learning environment, especially in teaching EFL students to write narrative paragraphs.